2022
DOI: 10.3390/ma15030781
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Dendritic Structure and Lattice Parameter of γ′-Phase in Single-Crystalline Turbine Blades Made of Superalloys

Abstract: The dendritic structure and the distribution of the γ′‑phase lattice parameter (aγ′) along selected lines of the longitudinal section in a model single-crystalline blade made of CMSX-4® nickel-based superalloy were studied. It was established that there is a correlation between the value of the aγ′ and the predomination of initial or ending fragments of the secondary dendrite arms. It is most noticed for the areas where the dendrite growth conditions are similar to steady. They are located in the center and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The current first part of the paper series concerns a longitudinal section intersecting both the selector extension area, treated as the reference area with the most negligible influence of the blade geometry on the γ lattice parameter and primary crystal orientation, and the nearest cooling bore. The paper is a continuation of our previous studies [38,[43][44][45], which have shown that at a longer distance from the selector, considering the top view, crystal misorientation and lattice parameter inhomogeneity increase significantly, which is related to the geometry of the blade and different other parameters, e.g., a technological parameter.…”
Section: Introductionmentioning
confidence: 69%
“…The current first part of the paper series concerns a longitudinal section intersecting both the selector extension area, treated as the reference area with the most negligible influence of the blade geometry on the γ lattice parameter and primary crystal orientation, and the nearest cooling bore. The paper is a continuation of our previous studies [38,[43][44][45], which have shown that at a longer distance from the selector, considering the top view, crystal misorientation and lattice parameter inhomogeneity increase significantly, which is related to the geometry of the blade and different other parameters, e.g., a technological parameter.…”
Section: Introductionmentioning
confidence: 69%
“…Figure 2 shows the graphs of the a γ′ (Z n ), α(Z n ), and β(Z n ) relationship obtained for the measuring line n. The value of a γ′ for the Z n ranged between 1 mm and 5.5 mm and varied about 3.5805 Å in the range of 0.001 Å, which corresponds to the fluctuations of a γ′ in an undisturbed dendritic structure [ 5 , 33 ]. However, for Z n equal to 6 mm, a γ′ decreases, and then, near Z n equal to 7 mm corresponding to the RA level, it increases by 0.002 Å, reaching the value of 3.5810 Å.…”
Section: Resultsmentioning
confidence: 99%
“…In the graph from Figure 4 a, some level I a γ′ changes in a range of 0.001 Å can be distinguished. These changes correspond to an undisturbed dendritic structure without significant bending of the dendrites [ 5 , 33 ] and, therefore, can be called fluctuations. Comparing the value of Z d1 equal to 6.5 mm, for which the fluctuation starts with the coordinates of changes occurring in the α(Z d1 ) graphs ( Figure 4 b), a correlation of the α maximum at Z d1 equal to 6.5 mm with a decrease in a γ′ (Z d1 ) greater than the fluctuation range near Z d1 equal to 6.5 mm can be observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nickel-based single-crystal superalloys have nickel-based solid solution γ phase matrix, where the γ phase (i.e., Ni3(Al, Ti, Ta)) is uniformly distributed, in concordance with [24,25]. Reed [26] The results of calculating the creep rate at the rupture point and the average creep rate in the working section during second creep stage are shown in Figure 11.…”
Section: Creep Behavior Of the Thin-walled Specimensmentioning
confidence: 94%